UNVEILING PROJECT MANAGERS’ COMPETENCIES IN GREEN VS. NON-GREEN CONSTRUCTION USING THE CRAWFORD INTEGRATED MODEL - Ismam, Jannatun Naemah; Mohd Zin, Ida Nianti; Khalil, Natasha (Journal of Surveying, Construction and Property, 2025)
The construction industry is undergoing a transformative shift toward sustainability, driving the need for specialized competencies among project managers in green construction projects. This study explores the critical differences in competencies required for managing green construction projects compared to non-green construction projects, using the Crawford Integrated Competency Model. Through an in-depth analysis, the classification matrix highlights the similarities and differences across competencies essential for effective project management in the green construction sector. The finding serves as a diagram for understanding the comprehensive skill set necessary for project managers operating in this specialized field, facilitating a clearer understanding of how knowledge, skills, and attitudes intersect in green construction project management. By identifying the core competencies required, this study provides a framework for professional development and training programs tailored to project managers in the green construction industry, ensuring that they possess the necessary attributes to succeed in the evolving landscape of sustainable building practices.